Kontribusi Kiai Dalam Penanaman Budaya Tasaamuh Di Pondok Pesantren - Husnullail, Muhammad; Mukhtar, Mukhtar; Anwar, Kasful; MY, Mahmud (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2024)
Islamic boarding schools are Islamic missionary and educational institutions in Indonesia. Since its inception, Islamic boarding schools have grown, developed and spread across various regions so that they have become a means of spreading Islamic teachings. Islamic boarding schools develop with a culture that has become a characteristic from the past until now. Kiai is a very influential figure in the survival of Islamic boarding school culture. Kiai as top managers can influence, mobilize and direct so that the behavior of students is in accordance with predetermined rules which will have an impact on the formation of Islamic boarding school culture. Islamic boarding school culture will specifically be discussed regarding the culture of Tasamuh/Tolerance in Islamic boarding schools. This ability or skill in carrying out tasks is what makes the kiai very influential in providing reinforcement and as a driving force to achieve the goals of the Islamic boarding school.